Soil Carbon Sequestration in Agroecosystems of India - Lal, Rattan (Journal of the Indian Society of Soil Science, 2015)
Soils of agroecosystems of India are degraded, depleted and severely devoid of the soil organic carbon (SOC) pool which is often